"Za slobodu nas Krist oslobodi" (Gal 5,1) - poimanje slobode u Poslanici Galaćanima : (II.: sloboda kao sloboda od Zakona) - Vidović, Marinko (Array, 2020)
Since the faith, and thus the freedom of the Galatians, is threatened by the attempt to return to the Law of Moses, relying on the biblical narrative of Abraham, Paul speaks of freedom as freedom from the Law of Moses. His basic claim is that the Law is not the beginning of the history of salvation, but Abraham’s faith, which relied on the promise of God. In this sense, the Law was added because of transgressions, because of the infancy of mankind; it was a supervisor in terms of the temporality and certain coercion of its subordinates and it was an enslaving force of which man had to be freed. This freedom was realized by God in Christ, who is the only true Abraham’s Descendant. Those who are in Christ have an Abrahamic relationship with God, a relationship of trust and reliance on the promise, a relationship of freedom which the Law did not serve but endangered it. Freedom is not realized under external compulsion, but by an inward commitment to God’s conduct, carried by his promise. In this part of the paper, in the Epistle to the Galatians we follow Paul’s thinking of the freedom God offers in Christ, which is based on the promise as the path to true freedom in responsibility. With Abraham as a model of God’s treatment of humanity and human response to God’s offer and promise, Paul defines freedom as freedom from the coercion of the Law.